Impact of obesity and epicardial fat on early left atrial dysfunction assessed by cardiac MRI strain analysis. Issue 1 (December 2016) - Evin, Morgane; Broadhouse, Kathryn; Callaghan, Fraser; McGrath, Rachel; Glastras, Sarah; Kozor, Rebecca; Hocking, Samantha; Lamy, Jérôme; Redheuil, Alban; Kachenoura, Nadjia; Fulcher, Greg; Figtree, Gemma; et al.
Abstract Background Diastolic dysfunction is a major cause of morbidity in obese individuals. We aimed to assess the ability of magnetic resonance imaging (MRI) derived left atrial (LA) strain to detect early diastolic dysfunction in individuals with obesity and type 2 diabetes, and to explore the association between cardiac adipose tissue and LA function. Methods Twenty patients with obesity and T2D (55 ± 8 years) and nineteen healthy controls (48 ± 13 years) were imaged using cine steady state free precession and 2-point Dixon cardiovascular magnetic resonance. LA function was quantified using a feature tracking technique with definition of phasic longitudinal strain and strain rates, as well as radial motion fraction and radial velocities. Results Systolic left ventricular size and function were similar between the obesity and type 2 diabetes and control groups by MRI. All patients except four had normal diastolic assessment by echocardiography. In contrast, measures of LA function using magnetic resonance feature tracking were uniformly altered in the obesity and type 2 diabetes group only. Although there was no significant difference in intra-myocardial fat fraction, Dixon 3D epicardial fat volume(EFV) was significantly elevated in the obesity and type 2 diabetes versus control group (135 ± 31 vs. 90 ± 30 mL/m2, p < 0.001). There were significant correlations between LA functional indices and both BMI and EFV (p ≤ 0.007). Conclusions LA MRI-strain may be a sensitive tool for the detection of early diastolic dysfunction in individuals with obesity and type 2 diabetes and correlated with BMI and epicardial fat supporting a possible association between adiposity and LA strain. Trials Registration Australian New Zealand Clinical Trials Registry No. ACTRN12613001069741